Effectiveness of alternative strategies to define index case phenotypes to aid genetic diagnosis of familial hypercholesterolaemia. Issue 3 (4th December 2012) - Clarke, Rosemary E J; Padayachee, Soundrie T; Preston, Rebecca; McMahon, Zofia; Gordon, Mitchell; Graham, Colin; Crook, Martin A; Wierzbicki, Anthony S
Abstract : Objective: To determine the utility of secondary stratification measures to improve the ascertainment of index cases of familial hypercholesterolaemia (FH). Design: A retrospective study of genotyped index patients with Simon Broome (SB) FH. Setting: University teaching hospital. Patients: 204 patients aged 55±14 years; 36% had tendon xanthoma (TX), 21% had coronary heart disease (CHD), low-density lipoprotein cholesterol (LDL-C) was 6.20±2.24 mmol/l and 55% had genetic FH. Interventions: The effects of different staging systems (SB vs Dutch criteria), presence of TX, use of LDL-C level, personal history of CHD and imaging evidence of atheroma by carotid intima-media thickness or coronary artery calcium score to identify genetic FH was explored. Outcome measures: Changes in C-statistic and net reclassification index (NRI). Results: SB criteria gave a C-statistic of 0.64 comprising C=0.65 in TX(+) and C=0.5 in TX(−) patients. Genetic FH was present in 75% of TX(+) compared with 44% in TX(−) patients. The Dutch criteria gave C=0.72. Addition of imaging criteria to prior CHD raised C=0.64 to C=0.65 in all patients with a NRI of 19% (p=0.06). In TX(−) patients imaging raised C=0.50 to C=0.65 with a NRI of 0.38 (p=0.001) and a weighted comparison index of 0.28, implying the detection of 14 more FH cases per thousand. Conclusions: Patients with tendon xanthoma (definite FH) should be genotyped. In patients with possible FH, the presence of a personal history of CHD or imaging evidence of increased atheroma offers the best method of identifying index patients likely to have monogenic FH.